Study on biological activities of extracted fractions from Typhonium flagelliforme (Lodd.) Blume - Quy Thuong, Le; Tuyet Mai, Bach; Minh Chau, Nguyen; Thi Phuong Hoa, Le; Quang Huy, Nguyen (VNU Journal of Science: Natural Sciences and Technology; Vol 33 No 2SDO - 10.25073/2588-1140/vnunst.4575, 2017)
Typhonium flagelliforme is a medicinal plant that has variety of uses. In medicinal traditional T. flagelliforme is used to treatment cough, headache, stomach pain chronic, and tracheitis. Moreover, use fresh bulbs treatment furuncle, the bites of poisonous insects. The active components in T. flagelliforme are flavonoids. In this study, the T. flagelliforme extract was obtained by methanol  to determine the chemical composition. Then, The extracts of methanol are extracted with polarization increases gradually solvents such as haxane, dichloromethane and ethyl acetate. Determination of antioxidant activity, cytotoxic activity of extracted fractions. Results obtained showed that the chemical compositions by the qualitative reaction preliminary were identified from T. flagelliforme containing reducing sugars, amino acids, organic acids, flavonoids, alcaloids, sterols. The antioxidant capacity of the ethyl acetate fraction reached 94.76 μg/ml, 10 times higher than the positive control is Quercetin. Cytotoxic activity of the haxane and diclomethane extracted fractions from T. flagelliforme exhibited cytotoxic activity on all three experimental cancers cell lines: KB, HepG2, Lu after 72h of culture with IC 50 values ​​range from 92.8 to 107.76 μg/ml. From dichlomethane extracted of T. flagelliforme was purified TF1 as Stigmast-4-en- 3-on.